Application of Fiber Grating Sensing in Similar Model Impact Tests of Underground Engineering. (14th April 2023) - Gao, Lei; Li, Zhihao; Li, Jie; Wang, Zhen; Jiang, Haiming; Wang, Mingyang
Abstract : To clarify damage or degradation mechanisms of underground shock disturbance of deep caverns, a customized model of a deep cavern to subjected ground shock was employed to simulate the following properties and processes: crustal stress loading, cavern excavation, and ground-shock disturbance loading. The similar model specimen was a cube of 1.3 m length and a size similarity ratio of 1 : 50. A fiber Bragg grating (FBG) strain sensor with multipoint distributions was developed to monitor the distribution of internal strains in the model. Sensors were appropriately arranged and packaged in the similar model of deep rock to determine strain variation in the model under hydrostatic confining pressure, construction dynamic load, and shock dynamic load. This investigation involved high crustal stress simulation, tunnel boring machine (TBM) construction simulation, and deep explosive shock simulation, respectively. The results suggest that the sensors can accurately monitor the strain during the entire process comprising loading, excavation, and shock generation and obtain the distribution of cave strain during excavation and shock generation. The cave strain indicated that the left and right sides of the tunnel both experienced a rapid increase in tensile strain from the top plane shock wave, proportional to the shock force. The mechanism of surrounding rock failure and the occurrence of the V-shaped blasting pit were clarified. In the model test, the following phenomena related to deep tunnel failure were simulated: particle ejection, block collapse, slabbing, and tunnel face collapse. The oscillatory wave was also monitored with FBG sensors. The results demonstrated that FBG strain sensor had good repeatability and could accurately monitor strain change in the different blocks, thus demonstrating considerable potential for use in similar model tests. The model tests conducted in this study can provide important technical reference and support for the construction and protective design of deep caverns.